Antidepressant Sales and the Risk for Alcohol-Related and Non-Alcohol-Related Suicide in Finland—An Individual-Level Population Study - Moustgaard, Heta (Public Library of Science, 2014)
OBJECTIVES: A marked decline in suicide rates has co-occurred with increased antidepressant sales in several countries but the causal connection between the trends remains debated. Most previous studies have focused on overall suicide rates and neglected differential effects in population subgroups. Our objective was to investigate whether increasing sales of non-tricyclic antidepressants have reduced alcohol- and non-alcohol-related suicide risk in different population subgroups. METHODS: We followed a nationally representative sample of 950,158 Finnish adults in 1995–2007 for alcohol-related (n = 2,859) and non-alcohol-related (n = 8,632) suicides. We assessed suicide risk by gender and social group according to regional sales of non-tricyclic antidepressants, measured by sold doses per capita, prevalence of antidepressant users, and proportion of antidepressant users with doses reflecting minimally adequate treatment. Fixed-effects Poisson regression models controlled for regional differences and time trends that may influence suicide risk irrespective of antidepressant sales. RESULTS: The number of sold antidepressant doses per capita and the prevalence of antidepressant users were unrelated to male suicide risk. However, one percentage point increase in the proportion of antidepressant users receiving minimally adequate treatment reduced non-alcohol-related male suicide risk by one percent (relative risk 0.987, 95% confidence interval 0.976–0.998). This beneficial effect only emerged among men with high education, high income, and employment, among men without a partner, and men not owning their home. Alcohol-related suicides and female suicides were unrelated to all measures of antidepressant sales. CONCLUSION: We found little evidence that increase in overall sales or in the prevalence of non-tricyclic antidepressant users would have caused the fall in suicide rates in Finland in 1995–2007. However, the rise in the proportion of antidepressant users receiving minimally adequate treatment, possibly due to enhanced treatment compliance, may have prevented non-alcohol-related suicides among men.